Model of integrative stomatology in neuroinformation space (Эндодонтия Today)
In article basic provisions of model of integrative stomatology are considered. On the basis of the researches conducted by authors regularity of integrative neurostomatosomatologic interactions in neuroinformation space of a human body in normal and pathologies is revealed.